Análise gravimétrica da viabilidade da implantação da coleta seletiva na UFCAT - (:unkn) unknown (Universidade Federal de Goiás, 2018)
Selective collection has proved to be a viable and economical alternative for the management of solid waste, among the many technical options developed in the last years because, through the awareness of the individuals involved, it allows the selection and referral of different materials to the recycling process. Through it, recyclable materials are separated from non-recyclable materials, showing that most waste can be recycled, no longer a source of environmental degradation, to become an economic and social opportunity, generating jobs and profit. Exaggerated consumption combined with urban growth has resulted in the generation of large quantities of solid waste. This is one of the major concerns of mankind, which, over the years, is always exposed to pollution and suffers damage from soil, water and air contamination. The greatest difficulty encountered by organizations in implementing selective waste collection is the awareness of people, the need to separate waste, the importance of reducing, reusing and recycling. The aim of the research was to diagnose the current situation and analyze the feasibility of implementing the selective collection of solid waste generated at the Federal University of Catalão (UFCAT). The research methods used were: field research, descriptive and quantitative, using the venn diagram and gravimetry, in order to quantify the data collected and respond to the proposed objectives. From the venn diagrams, it was identified that in blocks I and II, it is where it has the highest concentration of people during the periods, since all the courses have classes in these blocks, and in the morning period 422 people attend it, in the integral 1420 and at night 1118. Therefore during the day, I and II pass through 1,842 people, and in the total 2,960, people attend this block. The results of solid waste gravimetry showed that 51.8% of the solid waste generated is potentially recyclable waste composed of plastic (17.8%), nonferrous metals (17.4%) and paper / cardboard (16.7% %). The mass and volume balance estimated the potential for socioeconomic and environmental reintegration with a reduction of 51.8% of mass and 53.2% of volume of potentially recyclable waste in which separation at source and selective collection will reduce waste overload solid waste that is destined daily and without separation to the sanitary landfill of the municipality, it is still justified the implementation of the selective collection in the UFCAT for the infrastructure already installed, the same account with some own trash cans of the selective collection exposed on campus.
Analysis gravimetry of the viability of the implantation of the selective collection in UFCAT
Keywords: Resíduos sólidos; Coleta seletiva; Viabilidade; UFCAT; Gravimetria; Solid waste; Selective collect; Viability; UFCAT; Gravimetry; ENGENHARIAS::ENGENHARIA DE PRODUCAO